The Effect of Lecturers Pedagogic Competency on Accountability of Management Islamic Religious Higher Education - Norma Fitria (CV. Creative Tugu Pena, 2022)
Islamic Religious Higher Education Institutions are educational institutions whose implementation of learning is based on Islam. Higher education is a public institution where management and management must be carried out openly so that higher education management must be carried out where every sector in educational institutions must work together in providing knowledge in an open, balanced and responsible manner. Educators or lecturers at higher education institutions are required to have good lecturer competencies which will affect the accountability of Islamic religious college management. The aim of this research is to reveal the influence of lecturer competence on the accountability of Islamic religious higher education management. The type of research used descriptive qualitative methods, researchers use random sampling methods for data collection techniques. Based on the research findings, it is concluded that the pedagogic competence of Islamic religious college lecturers has a positive effect on the accountability of Islamic religious college management. The results obtained are t arithmetic 2.332 exceeding the t table value of 5% is 1.67. So that the greater the pedagogic competence of the lecturers, the greater the accountability value of higher education management. Keywords: Learning Outcome, Kalkulus Diferensial, Learning Method